Promoting Aspects of Discourse Macrostructure and Microstructure in EFL Expository Writing through Reading: A Case Study of Second Year Constantine University 1 Students - KOUICEM, Khadidja (Journal of Human Sciences, 2015)
The present study sets out to investigate the extent to which comprehension of discourse structure levels accounts for competence in EFL writing organization. More specifically, it seeks to enhance the students’ awareness regarding the significance of the macrostructure and microstructure notions in writing through reading   as a main source of language input and accumulation. The study has been conducted with two writing classes assigned to an experimental group and a control group. To compare the subjects’ performance in terms of the effective use of some aspects of discourse structure levels, a pre-test prior to a treatment and a post-test after the treatment have been administered in the form of in-class expository essays. Following the collection of the post-test essays, a questionnaire has been given to the experimental group subjects to elicit their opinions about the role of reading in the comprehension of discourse structure levels. The findings of the study have demonstrated a significant improvement of the experimental group in all aspects of discourse structure, while the control group has actually lowered its scores on some aspects and made insignificant improvement in others. Ultimately, the study has indicated that reading could be the best technique to develop the sense of discourse organization.